Association of hemoglobin levels with cause-specific and all-cause mortality among older adults: a prospective cohort study - Ni, Wenqing; Yuan, Xueli; Zhang, Yan; Zhang, Hongmin; Zheng, Yijing; Xu, Jian (Frontiers in Public Health, 2024)
BackgroundHemoglobin (Hb) optimal levels is clinically and biologically heterogeneous, data of older adults was not available.MethodsWe used data of participants enrolled in Shenzhen Healthy Ageing Research, in which the baseline Hb was measured in 223,407 older adults aged 65 or older to evaluation of Hb optimal levels. The vital status of the participants by 31 December, 2021 was determined. We estimated the hazard ratios with 95% confidence intervals for all-cause or cause-specific mortality using multivariable Cox proportional hazards models, and Cox models with restricted cubic spline (RCS) was used for all-cause mortality.ResultsOverall, 6,722 deaths occurred during a mean follow-up of 3.01 years from 2018 to 2021. The risk for all-cause and cause-specific mortality was significantly lower in males with Hb levels of ≥14.0 g/dL. The Hb range in which the lowest hazard ratios for the female all-cause or cardiovascular disease mortality were observed in our study was 12.0–14.9 g/dL and 11.0–14.9 g/dL, respectively. For the female participants observed higher Hb levels were significantly associated with lower risk of cancer-cause mortality (≥12.0 g/dL) or other-cause mortality (≥11.0 g/dL). The results from RCS curve showed similar results.ConclusionConsidering the risk of mortality, we recommended ≥14.0 g/dL and 12–14.9 g/dL as the optimal range of Hb among Chinese male and female older adults, respectively.